2019
DOI: 10.1038/s41589-019-0278-6
|View full text |Cite|
|
Sign up to set email alerts
|

MCC950 closes the active conformation of NLRP3 to an inactive state

Abstract: NLRP3 is an innate immune sensor contributing to the development of different diseases including monogenic autoinflammatory syndromes, gout, atherosclerosis, and Alzheimer’s disease. The molecule sulfonylurea MCC950 is a NLRP3 inflammasome inhibitor with potential clinical utility. However, the mechanism of action of MCC950 remains unknown. Here, we characterize the mechanism of action of MCC950 in both wild-type and autoinflammatory-related NLRP3 mutants, demonstrating that MCC950 closes the ‘open’ conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
287
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 329 publications
(308 citation statements)
references
References 32 publications
(32 reference statements)
19
287
0
2
Order By: Relevance
“…S1A,B). Also, as previously described [19,27], the pathological mutation of NLRP3 D303N associated with cryopyrin associated periodic syndromes (CAPS) resulted in spontaneous oligomerization of NLRP3 when expressed in HEK293 cells without any stimulation (Fig. 1C).…”
Section: Nlrp3 But Not Asc Oligomerize In Response To K + Effluxsupporting
confidence: 79%
“…S1A,B). Also, as previously described [19,27], the pathological mutation of NLRP3 D303N associated with cryopyrin associated periodic syndromes (CAPS) resulted in spontaneous oligomerization of NLRP3 when expressed in HEK293 cells without any stimulation (Fig. 1C).…”
Section: Nlrp3 But Not Asc Oligomerize In Response To K + Effluxsupporting
confidence: 79%
“…1C). In contrast, the NLRP3-specific inhibitor, MCC950 ( 14) , failed to prevent BTK-specific interaction and NLRP3 p-Y positivity (Fig. 1J).…”
Section: Resultsmentioning
confidence: 93%
“…The compound MCC950 (also known as CRID3) is the NLRP3 inhibitor that has been the most studied to date . MCC950 inhibits NLRP3 by directly interacting with the NLRP3 ATPase domain, thereby blocking ATP hydrolysis and NLRP3 oligomerization . Several studies have shown therapeutic efficacy of MCC950 in a variety of preclinical mouse models, including atherosclerosis, experimental autoimmune encephalomyelitis, diabetes, steatohepatitis, and colitis .…”
Section: Inflammasome‐targeted Therapies In Arthritic Diseasesmentioning
confidence: 99%
“…151,152 MCC950 inhibits NLRP3 by directly interacting with the NLRP3 ATPase domain, thereby blocking ATP hydrolysis and NLRP3 oligomerization. 151,153 Several studies have shown therapeutic efficacy of MCC950 in a variety of preclinical mouse models, including atherosclerosis, experimental autoimmune encephalomyelitis, diabetes, steatohepatitis, and colitis. 17 First, before its identification as a NLRP3 targeting molecule, MCC950 was discovered as an inhibitor of IL-1β activation.…”
Section: Nlrp3 Inhibitorsmentioning
confidence: 99%